2019
DOI: 10.1016/j.aller.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic profiles of patients with X-linked agammaglobulinemia from southeast Turkey: Novel mutations in BTK gene

Abstract: Our results show that mutations in southeast Turkey could be different from those in the rest of the world and molecular genetic tests are an important tool for early confirmed diagnosis of XLA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
1
5
0
1
Order By: Relevance
“…In a previously reported single center series on XLA from Chandigarh, arthritis was observed in 42% patients. Joint involvement in patients with XLA in present series was observed to be higher than that reported from United States, Argentina, Italy and Iran ( 24 , 26 , 28 , 30 ) but similar to that reported from Hong Kong (29%) ( 31 , 37 ), Mexico (38%) ( 35 ), Africa (37%), Turkey (22%) ( 27 ) and China (22%) ( 29 ) ( Table 3 ). It has been observed that patients with XLA who fail to maintain adequate trough levels despite IVIg replacement therapy are at higher risk of developing arthritis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In a previously reported single center series on XLA from Chandigarh, arthritis was observed in 42% patients. Joint involvement in patients with XLA in present series was observed to be higher than that reported from United States, Argentina, Italy and Iran ( 24 , 26 , 28 , 30 ) but similar to that reported from Hong Kong (29%) ( 31 , 37 ), Mexico (38%) ( 35 ), Africa (37%), Turkey (22%) ( 27 ) and China (22%) ( 29 ) ( Table 3 ). It has been observed that patients with XLA who fail to maintain adequate trough levels despite IVIg replacement therapy are at higher risk of developing arthritis.…”
Section: Discussionsupporting
confidence: 88%
“…In our previous study we had reported a mean delay of 4.2 years Delays in diagnosis are primarily a reflection of lack of awareness about PIDs among medical professionals as well as the laity. Diagnostic delays of upto several years have been noted in series from Latin America, Africa and the Middle East ( 24 27 ) ( Table 3 ). However, a greater delay in the diagnosis was noted in our scenario ( 20 ) emphasizing the need for concerted efforts to shorten this delay.…”
Section: Discussionmentioning
confidence: 99%
“…The tyrosine 545 is highly conserved (Figure ). The c.974 + 5G > A and c.179_181del (p.Lys60del) were previously described 25,26 …”
Section: Resultsmentioning
confidence: 99%
“…27 BTK tiene un papel crucial en la maduración de las células pre-B a células B maduras. 28 La función principal de esta proteína es promover la expansión de células pre-B en la etapa de pre-B1 a pre-B2. 29 Como resultado de la mutación en el gen BTK hay falla en el desarrollo de las células B y los pacientes afectados tienen niveles reducidos (< 1 %) de linfocitos B maduros XLA se hereda de forma vinculada al cromosoma X; BTK es el único gen conocido que lo causa.…”
Section: Agammaglobulinemia Ligada a Xunclassified